Active labour market policies in emerging adulthood may act as a protective factor against future depressiveness: an analysis of the long-term trajectories of depressive symptoms in the Northern Swedish Cohort - Virtanen, Pekka; Nummi, Tapio; Westerlund, Hugo; Östergren, Per-Olof; Janlert, Urban; Hammarström, Anne (Frontiers in Public Health, 2024)
Introduction. Drawing upon the framework of life course epidemiology, this study aligns with research on the mental health consequences of significant social transitions during early adulthood. The focus is on the variation in initial labour market attachment and the development of depressiveness, assuming that a firm attachment is associated with decreasing depressiveness.Methods. The baseline investigation of the studied cohort (n=1001) took place during their final year of compulsory schooling at age 16. Follow-up surveys were conducted at ages 18, 21, 30, and 43. Depressiveness was measured with a five-item score. Multiple trajectory analysis, incorporating five labour market statuses observed over seven half-year periods from ages 18 to 21, was employed to categorize the cohort into six distinct groups. Among these, 'All-time education,' 'From education to employment,' 'Education and employment,' and 'From employment to education' were considered to demonstrate firm labour market attachment. Meanwhile, 'Active labour market policy' and 'Unemployment' represented less firm attachment.Results. The trajectory of depressive symptoms amongof the total cohort from age 16 to age 43 exhibited a 'broken stick' pattern, reaching its lowest point at age 21. This pattern was evident in all groups classified as having a firm attachment. A substantial decrease in depressiveness was also observed in the relatively weakly attached 'Active labour market policy' group, whereas no 'broken stick' pattern emerged in the 'Unemployment' group. The disparities in the levels of depressiveness observed at age 21 remained relatively stable across the measurements at ages 30 and 43.Discussion. The results were as anticipatedexpected, except for the observed improvement in mental health within the 'Active labour market policy' group. supported labour market attachment during emerging adulthood can enhance mental well-being similarly to regular mainstream attachment. In terms of policy recommendations, the consistently high levels of depressiveness within the 'Unemployment' group underscoreemphasize the importance of imperative to reducinge long-term and repeated unemployment in young age. The findings regarding therelated to 'Active labour market policy' provide evidence of the intervention's benefits. While the primary goal of these measures is to create jobs for the unemployed, they also includeencompass elements that contribute to the participants' mental health.